Narrating Lives/Labour: Documenting Domestic Labour in Kolkata. Issue 4 (2nd October 2017) - Bhattacharya, Somdatta
ABSTRACT: The article deals with my work of reading the 'difficult lives' of female domestic workers in the city of Kolkata, India. The institution of domestic servitude in the city of Kolkata has always been fed by 'floating' labourers from the impoverished hinterlands. These women use the urban public transport network to travel for work. The study is based on the oral narratives of women domestic workers and touches upon various issues of gendered labour, women's negotiations of urban space, personal and collective memory and the ethics of life writing research. The personal interviews are supplemented by an archive of visual material in the form of photographs, hitherto unexplored. The interviews and the photographs give a peek into the difficulties of their lives and facilitate the attempt to collect recommendations from the grassroots. Considering that oral testimonies of unlettered domestic labourers largely remain unexamined as significant sources to understand the history of paid domestic labour in India, and the safety of women in public spaces – especially those who have to travel the cityscapes for work and are dependent on the 'public' transport network – is a major issue in urban India, such a study becomes crucial.